The Influence of Green School and Organizational Culture on Job Satisfaction and Environmentally Friendly Behavior - Lies Maisaroh; Rita Yuni Mulyanti; Didi Mulyadi (Inclusive Society and Sustainability Studies, 2023)
In the field of education, teachers are crucial to raising the standard of instruction. They play a crucial role in making sure that school events run well and serve as role models that pupils adore. The two main challenges educational institutions face are low job satisfaction among teachers and concerns about environmental influence. This study aims to determine the direct and indirect effects of implementing green school programs and organizational culture on job satisfaction and environmentally friendly behavior of Vocational High School (SMK) teachers.  This study employs quantitative research techniques. 211 teachers responded to a questionnaire that was used togather the data. The data obtained were analyzed using the Partial Least Squares (PLS) method. The results of the study found that green school did not affect job satisfaction, while organizational culture influenced job satisfaction. Job satisfaction affects environmentally friendly behavior. The green school does not affect environmentally friendly behavior either directly or through job satisfaction.  Environmentally friendly behavior is not directly influenced by organizational culture, but it is indirectly influenced by job satisfaction.  According to this study, job satisfaction can mediate the influence of organizational culture on employees' propensity to behave sustainably, but it cannot, as yet, do the same for the influence of green schools. This finding implies that in increasing the eco-friendly behavior of vocational teachers, school management needs to encourage an increase in teacher job satisfaction by paying attention to the organizational culture adopted by the school.